2010
DOI: 10.1007/s10549-010-1262-8
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution genomic profiling of male breast cancer reveals differences hidden behind the similarities with female breast cancer

Abstract: Male breast cancer (MBC) is extremely rare and poorly characterized on the molecular level. Using high-resolution genomic data, we aimed to characterize MBC by genomic imbalances and to compare it with female breast cancer (FBC), and further to investigate whether the genomic profiles hold any prognostic information. Fifty-six fresh frozen MBC tumors were analyzed using high-resolution tiling BAC arrays. Significant regions in common between cases were assessed using Genomic Identification of Significant Targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 49 publications
10
58
0
Order By: Relevance
“…In a paper characterizing male breast cancer tumors by comparative genomic hybridization, two distinct subgroups could be identified, which differed from genomic subgroups of female breast cancer. 5 Tumors in the larger male breast cancer subgroup displayed complex genomic profiles, significantly higher proliferation and were associated with a poor outcome. In the other study, characterizing male breast cancer tumors by gene expression, two male breast cancer subgroups largely corresponding to the comparative genomic hybridizationbased groups were identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a paper characterizing male breast cancer tumors by comparative genomic hybridization, two distinct subgroups could be identified, which differed from genomic subgroups of female breast cancer. 5 Tumors in the larger male breast cancer subgroup displayed complex genomic profiles, significantly higher proliferation and were associated with a poor outcome. In the other study, characterizing male breast cancer tumors by gene expression, two male breast cancer subgroups largely corresponding to the comparative genomic hybridizationbased groups were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these data, comparative genomic hybridization demonstrated significant differences regarding DNA aberrations compared with female breast cancer, and a new subgroup unique for male patients was identified. 5 Taking all these factors into account, these findings indicate that male breast cancer might be a separate tumor entity from female breast cancer.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The need for more refined therapeutic treatments for male breast cancer (MBC) is evidenced by a steady stream of publications highlighting gender-specific differences using IHC (1-5), genetics (6)(7)(8)(9)(10)(11), and more recently, epigenetics (12)(13)(14)(15). Of note, although MBC is similar histologically to female breast cancer (FBC), with the same panel of biomarkers used to guide treatment and prognosis, more rigorous interrogation of the underlying genetics shows heterogeneity in MBC as recognized in FBC where molecular profiling has identified different subgroups that correlate with varying clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The limited data published on male breast cancer indicate that there are genetic and phenotypic differences between male and female breast cancer. [2][3][4][5][6] Initially, prognosis in men was claimed to be poor with higher incidence of lymph node metastases at the time of discovery, but more recent studies showed that prognosis of male and female breast cancers corrected for stage and age is similar. [7][8][9] Although tumor size and lymph node status are independent prognosticators in male breast cancer, 9,10 there still is a need for more accurate outcome predictors of male breast cancer.…”
mentioning
confidence: 99%